Brick Lane a novel - Ali, Monica 1967- (Scribner, 2003)
Carrying into her adult years a sense of fatalism instilled during her hardscrabble birth, Nazneen finds herself married off to a man twice her age and moved to London, where she begins to wonder if she has a say in her own destiny.
Keywords: Bildungsromans; Bangladeshis -- England -- Fiction; Bildungsromans.; Women immigrants -- Fiction; Young women -- Fiction; Bangladesh -- Fiction; London (England) -- Fiction; Fiktionale Darstellung